1978
DOI: 10.1002/cjce.5450560301
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocracking of bitumen and heavy oils at CANMET

Abstract: A description of pilot-plant scale investigations of thermal and catalytic hydrocracking of bitumen and heavy oil at the Energy Research Laboratories, Canada Centre for Mineral and Energy Technology, is presented. A summary of division programs in the high pressure hydrogenation area since 1930, and current in-house and "contract" activities are outlined. his paper will document a long-term program of of a coker distillate derived from Athabasca bitumen"; Can. J. Chem. Eng.. 42. 170; 1961. ( 6 ) Booth F. L.. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The development of slurry phase catalysts, their hydroconversion mechanisms, and the main processes close to commercialization have been reviewed , and several slurry-phase hydroconversion processes aimed at residue oil upgrading have been developed over the last few decades. Examples include the M-coke process developed by Exxon in 1981, the CANMET process, the EST process (Eni Slurry Technology), VCC (VEBA Combi-Cracking), SOC (Super Oil Cracking), Intevep HDH Process , and the (HC) 3 process. , The difference between these processes is mostly in the type of catalyst used. Numerous studies have reported on the performance of the catalysts, both in terms of the active metal and in terms of the form of the catalyst added to the slurry-phase reactor. The performance of different metal sulfides, introduced to the reactor in the form of oil-soluble precursors, has also been reported. ,− The oil-soluble catalysts have superior activity compared to the activity of the catalysts added to the reactor as water-soluble salts or finely divided powders.…”
Section: Introductionmentioning
confidence: 99%
“…The development of slurry phase catalysts, their hydroconversion mechanisms, and the main processes close to commercialization have been reviewed , and several slurry-phase hydroconversion processes aimed at residue oil upgrading have been developed over the last few decades. Examples include the M-coke process developed by Exxon in 1981, the CANMET process, the EST process (Eni Slurry Technology), VCC (VEBA Combi-Cracking), SOC (Super Oil Cracking), Intevep HDH Process , and the (HC) 3 process. , The difference between these processes is mostly in the type of catalyst used. Numerous studies have reported on the performance of the catalysts, both in terms of the active metal and in terms of the form of the catalyst added to the slurry-phase reactor. The performance of different metal sulfides, introduced to the reactor in the form of oil-soluble precursors, has also been reported. ,− The oil-soluble catalysts have superior activity compared to the activity of the catalysts added to the reactor as water-soluble salts or finely divided powders.…”
Section: Introductionmentioning
confidence: 99%
“…These may differ depending on the feedstock. The feedstocks for production of synthetic crudes such as bitumens, heavy oils and refinery residua require upgrading (Pruden and Denis, 1977) which consists mainly of reactions reducing the average molecular weight. Further refining could include removal of heteroatoms in hydrotreaters but might also require less conventional treatment such as hydrocracking.…”
Section: Resultsmentioning
confidence: 99%
“…Gas formation increases with residue conversion in thermal hydrocracking of heavy oils and bitumens (Pruden, 1978). Table 2 indicated an increase in gas yields with increasing yield of naphtha and distillate fractions (Vol.…”
Section: Gas Formationmentioning
confidence: 99%